Clinical and Resource Utilization Patterns in Patients with Refractory Neuropathic Pain Prescribed Pregabalin for the First Time in Routine Medical Practice in Primary Care Settings in Spain. Issue 12 (30th October 2013) - Pérez, Concepción; Navarro, Ana; Saldaña, María T.; Masramón, Xavier; Pérez, María; Rejas, Javier
Abstract Context and Objective To describe clinical and resource utilization patterns in patients with refractory neuropathic pain (NeP) who were prescribed pregabalin for the first time in routine medical practice in primary care settings. Methods Post‐hoc analysis of a 12‐week prospective observational study including pregabalin naïve adult patients with refractory chronic NeP of at least 6‐months duration. Self‐reported pain intensity, disability, sleep disturbances, symptoms of anxiety and depression, disability, health‐related quality of life (HRQoL), health care resource utilization, and corresponding costs were assessed in this post‐hoc analysis. Results One thousand three hundred fifty‐four patients were enrolled in the study, and three treatment groups were identified: 1) 598 patients replaced prior pain treatments with pregabalin as monotherapy; 2) 589 added pregabalin to their existing pain treatments; and 3) 167 other pain treatments were prescribed according with physician routine medical practice. Statistically significant differences were reported at baseline for intensity of pain, patient disability, severity of depressive symptoms, and HRQoL (P < 0.01 in all cases). No statistically significant differences were reported among the three treatment groups for anxiety severity or sleep disturbances. Subjects who received add‐on pregabalin had greater use of direct and indirect resources vs the other groups, resulting in significantly higher quarterly overall costs per patient: €2, 397 (2, 308), €2, 470 (1, 857), and €3, 110 (2, 496), respectively (P < 0.001). Conclusion These findings suggest that primary care physicians chose pregabalin as an option for treating refractory patients who tended to have much more severe NeP profiles, costing society more than when they chose other therapeutic strategies not including pregabalin.